Aesthetics and subjectivity : from Kant to Nietzsche - Bowie, Andrew, 1952- (Manchester University Press, 2003)
New, completely revised and re-written edition. Offers a detailed, but asccesible account of the vital German philosophical tradition of thinking about art and the self. Looks at recent historical research and contemporary arguments in philosophy and theory in the humanities, following the path of German philosophy from Kant, via Ficthe and Holderlin, the early Romantis, Schelling, Hegel, Scleimacher, to Nietzsche. Develops the approaches to subjectivity, aesthetics, music and language in relation to new theoretical developments bridging the divide between the continental and analytical traditions of philosophy. The huge growth of interest in German philosophy as a resource for re-thinking both literary and cultural theory, and contemporary philosophy will make this an indispensible read.